Adaptacja działalności ekonomicznej do procesów metabolizmu ekosystemów podstawą zrównoważonego rozwoju - Ryszkowski, Lech (Adaptation of economic activity to the ecosystem metabolism as a basis for sustainable development, 2007)
Until recently, specialist knowledge creating new technologies and economic activity have been considered as two main drivers of social development. Increasing pressure on natural habitats to provide for the growing number of people livelihood needs led to different environmental, economic, and social threats for which the evolution of the EU Common Agricultural Policy (CAP) can be a good experimental example. Its preliminary success caused soon the food overproduction which entailed negative socio-economical problems and progressing degradation of water, soils and agricultural landscapes. As a result its modification became necessary by the acceptation of the sustainable development concept, based on the integration of ecological (environmental), economic, and social processes, as three main pillars of the human activity. Ali processes of the geosphere are conditioned by the changes of solar Energy fluxes, matter cycling and mechanisms of their regulation. These are the driving processes not only for organisms but also for ecosystems’ functioning. The Millennium Ecosystem Assessment finished in 2005 yielded with the generał recognition and hierarchical arrangement of ecosystem services, that determine not only human life but also the course of economicj and social processes. Four main categories of the services could be arranged as follows: 1 – basie services that determine all others; 2 - productive; 3 - regulative; 4 - cultural. The proper composition of different ecosystems in the landscape allow to optimize productive services with regulative ones, that enables coexistence of intensive production with environment protection. The closer will the management be agreed with the course of natural processes, the morę successful will be achievements of the sustainable development tenets.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1190, s. 181-190